2013
DOI: 10.1073/pnas.1315133110
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of WC-independent frequency transcription by RCO-1 is essential for Neurospora circadian clock

Abstract: Rhythmic activation and repression of clock gene transcription is essential for the functions of eukaryotic circadian clocks. In the Neurospora circadian oscillator, frequency (frq) transcription requires the WHITE COLLAR (WC) complex. Here, we show that the transcriptional corepressor regulation of conidiation-1 (RCO-1) is essential for clock function by regulating frq transcription. In rco-1 mutants, both overt and molecular rhythms are abolished, frq mRNA levels are constantly high, and WC binding to the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 54 publications
5
56
0
1
Order By: Relevance
“…Our previous work has shown that there is WC-independent frq transcription in rco-1 KO mutants (1). Moreover, the constitutive transcription of WC-independent frq interferes with the negative feedback loop and disrupts the circadian oscillator in rco-1 KO mutants.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our previous work has shown that there is WC-independent frq transcription in rco-1 KO mutants (1). Moreover, the constitutive transcription of WC-independent frq interferes with the negative feedback loop and disrupts the circadian oscillator in rco-1 KO mutants.…”
Section: Discussionmentioning
confidence: 95%
“…Chromatin Immunoprecipitation-ChIP assay was performed as described previously (1,25,36,38). Briefly, Neurospora tissues under the experimental conditions were fixed with 1% formaldehyde for 15 min at 25°C with shaking, the fixation reaction were stopped by adding 125 mM glycine with shaking for another 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we recently discovered that frq transcription can occur in a WC-independent manner, and the suppression of the WC-independent frq transcription by RCO-1 is essential for circadian clock function (29). The homolog of RCO-1 in Saccharomyces cerevisiae is Tup1, a component of the Tup1-Ssn6 complex that represses gene expression (30,31).…”
mentioning
confidence: 99%